Anti-aggregant therapy in patients with coronary heart disease and gastric ulcer - A. B. Sumarokov; L. I. Buryachkovskaya; M. V. Ezhov; I. A. Uchitel’; Yu. V. Dotsenko (Кардиоваскулярная терапия и профилактика)
Aim. To evaluate primary haemostasis parameters during two-month Zyllt therapy in patients with coronary heart disease (CHD) and gastric ulcer. Material and methods. In 60 patients with CHD, hyperlipidaemia, and gastric ulcer in remission, the effects of Zyllt (clopidogrel), in combination with lipid-lowering Vasilip (simvastatin) treatment, were investigated. Antiaggregant effects of Zyllt were assessed by measuring spontaneous and ADP-induced platelet aggregation at baseline, 5 days and 2 months after the therapy start. At baseline and in the end of the study, total blood cell count, lipid profile, and the levels of hepatic enzymes and C-reactive protein were examined. Results. Without the loading dose administration, the anti-aggregant effect of Zyllt was moderate at Day 5. In 37,2 % of the patients, all aggregation parameters were normalized, while in the other participants, they remained elevated. After 2 months of the treatment, aggregation parameters normalized in 78,7 %, and remained elevated in 20,7 % (n=12). Among these 12 individuals, no spontaneous aggregation was observed in 7, while ADP-induced aggregation substantially decreased, as a marker of Zyllt effects on its therapeutic target. In addition, Vasilip demonstrated good lipid-lowering effect in the study participants. Conclusion. Zyllt is an effective anti-aggregant, which is well-tolerated, without inducing hypocoagulation. In case of combined therapy, both lipid-lowering effect of Vasilip and anti-aggregant effect of Zyllt were observed. This combination did not result in hepatic or renal disturbances, or increased risk of cardiovascular events. The effectiveness of anti-aggregant therapy could be assessed by monitoring platelet aggregation.